Augmentation of Venous Drainage in Deep Inferior Epigastric Perforator Flap Breast Reconstruction: Efficacy and Advancement - Xin, Qiang; Luan, Jie; Mu, Hua; Mu, Li (Journal of Reconstructive Microsurgery, 2012)
Deep inferior epigastric perforator flap (DIEP) is the workhorse for autologous breast reconstruction because it is associated with less abdominal wall donor site morbidity; however, the high incidence of venous congestion of zone IV within the DIEP flap is the most important disadvantage. Venous augmentation may be an appropriate method for venous decompression of the DIEP flap. This study aims to assess retrospectively the efficacy of the venous augmented DIEP flap and to present an advanced technique for venous augmentation. A total of 79 breast reconstructions using DIEP flap from January 2006 to March 2011 were included. Thirty-two patients who underwent venous augmented DIEP flap were selected as the test group, and 47 patients who underwent the traditional DIEP flap were included as the control group. Three indices—operation time, flap size, and flap complication rate—were compared between the two groups. The operation time was 6.6 ± 0.7 hours in the test group and 6.1 ± 1.2 hours in the control group (p < 0.05). The mean flap size was 325.9 ± 20.6 cm2 in the test group and 294.7 ± 24.2 cm2 in the control group (p <0.05). In the test group, there was one partial flap loss (complication rate was 3.1%). In the control group, the total complication rate was 10.6% (p <0.05). Venous augmentation can successfully enhance the viability of a DIEP flap. The SIEV-SIEV (superficial inferior epigastric vein) reverse-flow anastomosis is an efficient and convenient method of venous augmentation for DIEP flap, with negligible drawbacks.
Keywords: breast reconstruction; DIEP; venous augmentation; flap congestion